In vitro optoacoustic flow cytometry with light scattering referencing - Markus Seeger (Nature Portfolio, 2021)
Abstract Morphological and functional optoacoustic imaging is enhanced by dedicated transgene reporters, in analogy to fluorescence methods. The development of optoacoustic reporters using protein engineering and directed evolution would be accelerated by high-throughput in-flow screening for intracellular, genetically encoded, optoacoustic contrast. However, accurate characterization of such contrast is impeded because the optoacoustic signals depend on the cell’s size and position in the flow chamber. We report herein an optoacoustic flow cytometer (OA-FCM) capable of precise measurement of intracellular optoacoustic signals of genetically-encoded chromoproteins in flow. The novel system records light-scattering as a reference for the detected optoacoustic signals in order to account for cell size and position, as well as excitation light flux in the focal volume, which we use to reference the detected optoacoustic signals to enhance the system’s precision. The OA-FCM was calibrated using micrometer-sized particles to showcase the ability to assess in-flow objects in the size range of single-cells. We demonstrate the capabilities of our OA-FCM to identify sub-populations in a mixture of two E. coli stocks expressing different reporter-proteins with a precision of over 90%. High-throughput screening of optoacoustic labels could pave the way for identifying genetically encoded optoacoustic reporters by transferring working concepts of the fluorescence field such as directed evolution and activated cell sorting.